Comprehensive Evaluation of Production Water Footprint in Shandong Province - ZHANG Min; ZHANG Yu; TIAN Qing; WANG Mengfan (Renmin Zhujiang)
As a significant economic and populous region, Shandong Province also grapples with water scarcity.The water footprint concept provides a fresh understanding of water resources, revealing the true utilization extent of the resources.A model and evaluation system for measuring the production water footprint is established to assess water resource utilization in the province from 2010 to 2021.The results indicate that the production water footprint in the studied region experiences fluctuations and presents an overall increasing trend during this period, with higher levels in the western and southern regions and lower ones in the eastern and northern areas.The blue, green, and grey water footprints all display a rising trend.Agriculture accounts for the largest proportion among all the sectors.From a comprehensive perspective, the economic benefits of the production water footprint steadily increase, but the per capita carrying capacity of the production water footprint is relatively poor, with a relatively large water resource pressure index.Generally, Shandong faces unsustainable water resources and considerable water pressure, which highlights the need for timely measures to adjust the industrial structure, enhance water-saving technologies, and improve pollution prevention and control to alleviate current water scarcity.